Skin manifestations in spondyloarthritis - Meier, Katharina (Ther Adv Musculoskelet Dis, 2020)
Spondyloarthritides (SpA) like psoriatic arthritis, axial spondyloarthritis/ankylosing spondylitis, reactive arthritis and inflammatory bowel disease (IBD)-associated SpA can present with characteristic skin manifestations. These SpA-associated skin disorders may precede joint involvement, reflect a loss of efficacy of a current systemic treatment or can even be treatment associated. Cutaneous manifestations in SpA not only add additional morbidity with physical impact but also impose a psychosocial burden on affected patients. Psoriasis (PsO) – the main skin disease in SpA – has a variety of clinical presentations, including plaque-type PsO, inverse PsO, guttate PsO, erythrodermic PsO, nail PsO and pustular types. SpA associated with IBD presents with neutrophilic and granulomatous skin disorders, including pyoderma gangrenosum, hidradenitis suppurativa and cutaneous Crohn’s disease. Reactive arthritides has a favourable prognosis and may feature keratoderma blenorrhagicum or balanitis circinatum as typical skin manifestations. Immunologically, SpA-associated skin diseases share interleukin (IL)-17 and IL-23 dysregulation but show distinctive genetic and immunological profiles. Therefore, they vary in their treatment responses to targeted therapies with biologicals or small molecules. In this review, we highlight the clinical presentation of skin manifestations in SpA and discuss therapeutic approaches in this interdisciplinary field.